Błędy w zapisie fonemów samogłoskowych języka polskiego (Conversatoria Linguistica, 2022)
The article approaches the subject of spelling errors made in notation of vowel phonemes of the Polish language. The focus group consisted of Polish teenagers aged 15 or 16 years who were asked to produce a sample writing in the form of an argument and to write a dictation, devised by the author himself. The article comprises four parts: the introduction, the typology of spelling errors, the description of spelling errors seen from the perspective of phoneme-grapheme correspondences, and the discussion part. Most of the collected errorscollected were of orthographic (phonetically correct) or morphological type, depending on the chosen classification. Of the gathered material, substituting the ę grapheme with e in the ę - /ɛ/ word-final position (such as Ja chcę – eng. ‘I want’) was the most prevalent pattern. Other errors concerned mainly: incorrect spellings of the /u/ phoneme (especially in a context where the ó grapheme does not alternate with the o grapheme), wrong spellings of the ął, ęł, ęl, and en biphonematic group (as in wziął, wzięła, wzięli, argument), as well as confusing the om and ą graphemes in their word-final position (e.g. kolegom, kolegą eng. ‘a friend’ respectively in its dative and ablative grammar case).